Businesswomen in Germany and their performance by ethnicity: it pays to be self-employed - Amelie F. Constant (Institute for the Study of Labor (IZA), 2008)
In this paper I assert that the entrepreneurial spirit can also exist in salaried jobs. I study the determinants of wages and the labor market success of two kinds of entrepreneurial women in Germany - self-employed and salaried businesswomen - and investigate whether ethnicity is important in these challenging jobs. Employing data from the German Socioeconomic Panel I estimate selection adjusted wage regressions for both types of businesswomen by country of origin. I find that self-employment offers businesswomen a lucrative avenue with higher monetary rewards, albeit for a shorter spell. If salaried businesswomen went into self-employment, they would receive considerably higher wages and for at least 30 years. However, if self-employed businesswomen went into salaried jobs, their wages would decline, suggesting that it is the self-employment sector that offers better opportunities and monetary success. Self-employed women in Germany fare well and most importantly, success does not depend on their ethnicity.
urn:nbn:de:101:1-20080825214
Keywords: M13; 330; Businesswomen; entrepreneurship; self-employment; economics of minorities; immigrants wage differentials; Weibliche Führungskräfte; Selbstständige; Unternehmer; Lohn; Ethnische Gruppe; Lohndifferenzierung; Deutschland